A Review On Cassia Fistula - Bhandari, Sanjay Singh; Khurana, Kunal; Balyan, Ankur; Kabra, Mahaveer Prasad; Negi, Kapil (Asian Journal of Pharmaceutical Research and Development, 2013)
Cassia fistula (Fabaceae–Pea family) has traditional medicinal value eg. used in cooling, purgative, anthelmintic, emetic, diuretic, depurative, skin diseases, burning sensation, dry cough and bronchitis etc. the various plants parts such as roots, flower, seeds are used to solve above purpose. The chemical constituents, kaempferol, rhein, bianthroquinone glycoside, alkoloids, gkutin, pectin, calcium, oxalates, flovefin and anthraquinone obtained from the different parts of the plant. Hepatoprotective, antioxidant, hypoglycemic, antibacterial, anti-inflammatory activity was reported for Cassia fistula.